Transitioning urban experiments. Reflections on doing action research with urban labs. - Scholl, Christian; Kraker, Joop de; Hoeflehner, Thomas; Wlasak, Petra; Drage, Thomas; Eriksen, Mette Agger (Oekom, 2018)
There is a large diversity in lab approaches. We contribute to a much needed evaluation by reflecting on a specific transdisciplinary action research approach that transforms a conventional innovation project into a transition experiment. We show how the approach could be adapted in order to be applied to urban labs focusing on sustainability transitions in governance systems. Urban labs have gained popularity throughout Europe. They are a manifestation of the search for new forms of urban governance capable of addressing the complex problems that cities are facing nowadays. These labs typically aim to create space for transdisciplinary research, co-creation and experimenting with potential solutions to sustainability challenges. In urban labs in four European cities, we applied a specific transdisciplinary action research approach labelled as "transitioning of (urban lab) experiments". Our approach consists of four steps: co-design of experiments, setting explicit learning goals, evaluating what has been learned, and dissemination and embedding of lessons learned. Critically reflecting on the difficulties encountered in the implementation of the transitioning approach, we conclude that it must be adapted when applied to urban labs focusing on sustainability transitions in institutional and governance systems rather than in socio-technical systems. We provide recommendations as to how the approach could be adapted.
Keywords: Nachhaltige Entwicklung; Stadtentwicklung; Urban Governance; Transformation; Umsetzung; Schnittstelle; Wissenschaft; Gesellschaft; Methode; Forschungsmethode; Wissenstransfer; Reallabor; Experiment; Projekt; Vergleich; Reflexion; Transdisziplinarität; Aktionsforschung